2020
DOI: 10.2131/fts.7.115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen on fatty-acid-induced cytotoxicity in mouse Neuro-2a neural cells

Abstract: The accumulation of free fatty acids induces lipotoxicity in neural cells. Estrogen, 17βestradiol (E2) protects against the damage of cells in various organs and tissues. However, the role of E2 on lipotoxicity in neural cells remains unclear. In this study, we investigated the effects of E2 on stearic acid (saturated fatty acid)-and oleic acid (unsaturated fatty acid)-induced cytotoxicity in retinoic acid-induced mouse neuroblastoma Neuro-2a differentiated into neural cells. Cell viability was evaluated by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Several studies suggested that estrogen may ameliorate lipotoxicity-induced adverse effects in various cell types, such as hepatocytes and hippocampal astrocytes (Frago et al, 2017;Galmés-Pascual et al, 2020). We recently found that estrogen prevented fatty acid-induced cell death in neural cells (Ogawa et al, 2020). This suggests that estrogen could have inhibitory effects on cell damage in the sciatic nerves, however the protective mechanisms induced by estrogen in sciatic nerves are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that estrogen may ameliorate lipotoxicity-induced adverse effects in various cell types, such as hepatocytes and hippocampal astrocytes (Frago et al, 2017;Galmés-Pascual et al, 2020). We recently found that estrogen prevented fatty acid-induced cell death in neural cells (Ogawa et al, 2020). This suggests that estrogen could have inhibitory effects on cell damage in the sciatic nerves, however the protective mechanisms induced by estrogen in sciatic nerves are still unknown.…”
Section: Discussionmentioning
confidence: 99%